Aspects of nursing student placements associated with perceived likelihood of working in residential aged care. Issue 5 (8th November 2015) - Lea, Emma; Mason, Ron; Eccleston, Claire; Robinson, Andrew
Abstract : Aims and objectives: To investigate which aspects of student nurses' experiences of residential aged care facility clinical placements affect perceived likelihood of choosing a career in residential aged care post graduation. Background: Poor clinical placement experiences as a student contribute to nurses' reluctance to work in aged care. Various factors have been found to improve the placement experience and influence students' attitudes and employment intentions. Missing from the literature is a quantitative – rather than qualitative – exploration of which attributes of an aged care placement link to perceived likelihood of working in residential aged care post graduation. Design: Supported residential aged care placement programmes were developed for nursing students using an evidence‐based best‐practice model within an action research framework. Staff formed a mentor group in two facilities. During placement, weekly feedback meetings were held for students and mentors. Methods: Second‐year nursing students ( n  =   71) participating in a three‐ or four‐week placement programme at two Tasmanian residential aged care facilities (September 2011–May 2013) completed questionnaires on placement experiences. Measures of association (correlation coefficients) were used to assess the effect of a range of variables on the likelihood of working in an aged care facility post graduation. Results: Associations were identified between the likelihood of working in residential aged care post graduation and nurse mentor–student feedback exchange, Teaching and Learning Score and supportiveness of care workers. Conclusions: This study adds to the literature by providing quantitative evidence that certain aspects of aged care placements influence attitudes to working in these sites post graduation. Relevance to clinical practice: To increase interest in working in residential aged care, the teaching and learning environment needs improvement, opportunities should be proffered for mentor–student feedback exchange during placements and care workers need support to mentor effectively.